Review of the mechanical failure of non-combustible facade systems in fire. (26th December 2022) - Lugaresi, Francesca; Kotsovinos, Panagiotis; Lenk, Peter; Rein, Guillermo
Highlights: Review of fire performance of facades with stone, concrete, metal and glass panels. Definition of typical facade support structure and their fire performance. Study of material parameters that effect the fire behaviour of facade systems. Comparison of material performance and thermal expansion at high temperature. Abstract: Fires involving the facade of a building are a modern and complex problem. Previous reviews on fire safety of facades have addressed flammability and fire spread, but these are not the only hazards. Mechanical failure can cause portions of the facade to fall out, threatening people evacuating and emergency personnel, and causing damage at lower heights. In this paper we undertake a review of the state-of-the-art concerning the mechanical behaviour of facades in fire and their failure mechnisms. We describe the different support systems, including curtain walls, which are essential to maintaining the integrity. We compare the mechanical and thermal properties that influence failure of non combustible components such as stone, concrete, metal, and glass panels, and discuss the behviour of typical connections. The most vulnerable elements are identified and their possible failure modes are discussed, thus allowing a better understanding of the safe design and construction of facades. The present discussion could aid researchers develop projects that have a greater impact for the industry.